Study interplay between Asprosin with Vitamin D in metabolic syndrome - Mohammed , Shaha Abdallha; Allwsh , Thikra Ali (Journal of Contemporary Medical Sciences, 2022)
Objective: The study aims to in investigating the role of the asprosin hormone and its relationship with vitamin D in patients with metabolic syndrome and clinical parameters. Methods: The study included measurement asprosin hormone, vitamin D, and some biochemical variable levels in metabolic syndrome patients with age matching to the control group (35 - 65 years). The study includes (95) samples of metabolic syndrome patients [49female, 46 males] who were attending the abdominal consultation unit at the Ibn Sina Teaching Hospital in Mosul, Iraq . MetS were diagnosed in compliance with the criteria of the NCEP (ATP III) and AHA/ NHLB . Samples were collected during the period from January 2021 to December 2021. Also, the study was carried out on 76 samples of apparently healthy (40 female, 36 male) as a control group. Results: The findings revealed a significant increase in the concertation of the asprosin hormone in metabolic syndrome patients compared to the control group. Also, it has been found that was a significant increase in the concertation of fasting glucose, insulin, homeostasis model for insulin resistance (HOMA-IR), Triglycerides , low-density lipoprotein-cholesterol, very low-density lipoprotein-cholesterol , total cholesterol and urea. In addition to a decline in high-density lipoprotein cholesterol , non-high-density lipoprotein cholesterol (Non-HDL), (HOMA-B ), vitamin D and Calcium among metabolic syndrome patients. there is also a significant inverse correlation between asprosin hormone with the Vitamin D. Conclusion: The study concluded that the hormone asprosin is a good indicator that reflects the status of metabolic syndrome patients and vitamin D appeared to be associated with MetS, as well as the Insulin resistance (IR) and lipid profile.